The ultimate sales machine : Turbocharge your business with relentless focus on 12 key strategies - Holmes, Chet, ....- (The penguin groupe : New York, 2007)
Chet Holmes has been called "America's greatest business growth expert." He helps his clients blow away both the competition and their own expectations. And his advice starts with one simple concept: focus! what if you could double your appointment-setting skills? What if you could get nine times more clients pouring into your business for the same marketing dollars? Instead of trying to master four thousand strategies, zero in on the handful of essential skills that, once mastered, can transform your business.
Keywords: Verkoop